Small RNA and degradome profiling involved in seed development and oil synthesis of Brassica napus - Wei, Wenhui; Li, Gan; Jiang, Xiaoling; Wang, Yuquan; Ma, Zhihui; Niu, Zhipeng; Wang, Zhiwei; Geng, Xinxin (PloS one, 2018)
MicroRNAs (miRNAs) play a prominent role in post-transcriptional gene expression regulation and have been involved in various biological and metabolic processes to regulate gene expression. For Brassica napus, improving seed-weight and oil-content is the main breeding goal. In order to better understand the regulation mechanism of miRNAs during seed-weight formation and oil-content accumulation in B. napus, in this study, a high-throughput sequencing technology was used to profile miRNAs expression of Brassica napus immature seeds from one to six weeks after flowering. A total of 1,276 miRNAs, including 1,248 novel and 28 known miRNAs, were obtained from both the high-seed-weight with low-oil-content RNA pool (S03) and the low-seed-weight with high-oil-content RNA pool (S04). Analysis of their expression profiles disclosed that 300 novel and two known miRNAs were differentially expressed between S03 and S04. For degradome analysis, 57 genes with 64 degradation sites were predicted to be targeted for degradation by these miRNAs. Further bioinformatics analysis indicated that these differentially expressed miRNAs might participate in regulation of myriad cellular and molecular processes, during seed development and oil synthesis. Finally, 6 target genes with potential roles in regulation of seed development and 9 other targets in seed oil synthesis, were further confirmed as candidate genes from small RNA and degradome sequencing.